The numbers of waterfowl in Estonia - Onno, Sven (Wildfowl, 1965)
About 27,000 pairs of ducks of 14 species, 500 pairs of Greylag Geese and 10 pairs of Mute Swans have bred annually in Estonia in recent years. Mallard (10,000 pairs) are most numerous, though they and Velvet Scoters (1,100) and Pochard (400) are decreasing. Eiders (3,500 pairs), Shoveler (2,500) and Scaup (90) are increasing. Much larger numbers occur on passage in spring and autumn, including over a million Long-tailed Ducks and Velvet and Common Scoters, over 100,000 Bean Geese and over 50,000 Whooper Swans. Few wildfowl winter, 3,000 Mallard being the most plentiful.